ORIGAMI AS AN EDUCATIONAL TOOL AND ITS EFFECT ON THE DEVELOPMENT OF SCHOOL STUDENTS - Mohd Salehudin Marji; Nor Aisyah Che Derasid; Aede Hatib Musta'amal; Ade Aliff Jobin (Sean Institute, 2023)
In recent years, origami has also made its way into the field of education. Many countries have implemented origami in their educational curricula due to its numerous benefits for student development. Origami has been found to help students in many ways, including the development of cognitive, social, and motor skills. To investigate the effects of origami on student development, a study was conducted using a systematic literature review method. The study focused on articles published between 2018 and March 13, 2023, and utilized keywords such as